2012
DOI: 10.1002/dvdy.23782
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 inactivation extends proliferation and alters histogenesis in the postnatal mouse retina

Abstract: Background The cell cycle regulator Cyclin D1 is expressed in embryonic retinal progenitor cells (RPCs) and regulates their cell cycle rate and neurogenic output. We report here that Cyclin D1 also has important functions in postnatal retinal histogenesis. Results The initial production of Müller glia and bipolar cells was enhanced in Cyclin D1 knockout (Ccnd1−/−) retinas. Despite a steeper than normal rate of depletion of the RPC population at embryonic ages, postnatal Ccnd1−/− retinas exhibited an extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Fig. S3D) and adult mouse retinas (Das et al, ; Osakada et al, ). Interestingly, in EGF‐stimulated retinas Ccnd3 remains expressed and even more Ccnd3+ are generated until DEV12 (Supp.…”
Section: Resultsmentioning
confidence: 98%
“…Fig. S3D) and adult mouse retinas (Das et al, ; Osakada et al, ). Interestingly, in EGF‐stimulated retinas Ccnd3 remains expressed and even more Ccnd3+ are generated until DEV12 (Supp.…”
Section: Resultsmentioning
confidence: 98%
“…We next asked how RPC proliferation is supported in the absence of SOX2. D-type Cyclins are expressed in RPCs and promote progression through the cell cycle [ 51 53 ]. We examined expression of CyclinD1 and CyclinD3 protein by immunofluorescence in control and mutant OCs at E16.5 and P0.…”
Section: Resultsmentioning
confidence: 99%
“…CyclinD3 protein was confined to the prospective CE of controls but expanded into the central OC of mutants (Figure 7 G, H versus J, K). Co-labeling with CyclinD1 and CyclinD3 indicated that these two proteins, which are normally mutually exclusive, were aberrantly co-expressed in some Sox2 -depleted cells (Figure 7 M-P; arrows) [ 53 ].
Figure 7 D- type Cyclins are aberrantly expressed in Sox2- ablated optic cup progenitor cells (OCPCs) at E16.5.
…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this explanation are the phenotypes reported in several cell cycle mutants that alter the dynamics of cell cycle progression. For example, loss of cyclin D1, a protein that controls cell cycle transition from G1 to the S-phase, results in a loss of RGCs and an increase in the fate of late-born cells (12). Similarly, loss of cyclin D2 alters the cell cycle duration of the cells within the ciliary marginal zone, resulting in a reduction in the ipsilateral and contralateral RGC population (32).…”
Section: Cell Cycle and Neurogenesismentioning
confidence: 99%
“…Thus, cell cycle components are able to drive the cellular processes during retinal neurogenesis and are key regulators of cell fate specification (9,10). Factors that promote cell cycle progression like cyclins and cyclin-dependent kinases are highly expressed in the RPCs, but their expression is down-regulated in the differentiated retinal cells, consistent with a function in maintaining cell proliferation (11)(12)(13). Conversely, cyclin-dependent kinase inhibitors are involved in promoting cell cycle exit, and their loss can result in increased proliferation (14,15).…”
mentioning
confidence: 99%